“Incidencia de la carga de trabajo en la satisfacción laboral de los miembros del servicio policial de la UPC del cantón La Maná”. - Ojeda Sánchez, Tania Abigail (2022)
The general objective of this research project was to analyze the incidence of the workload on the job satisfaction of the police service’s members of the UPC in La Maná canton for the improvement of the administrative and operational management. To fulfill it, a mixed focus was required, from the qualitative perspective, the reality was described which is based on the criteria and opinions of who are involved in the existing problem. From the quantitative approach, the existence of incidence between the variables workload and job satisfaction was determined. The types of field and bibliographic research, the logical, deductive, and synthetic analytical historical methods were used. Quantitative approach was immersed through a correlational level and statistical procedures carried out by the IBM SPSS 25 program, taking as input the obtained results in the surveys applied to 94 police officers of the UPC in the La Maná canton. They constituted the population under study. The used instrument was structured by 34 questions which corresponded to workload, and whose contemplated the factors: mental demand, physical demand, level of effort, job performance, frustration; the variable job satisfaction was divided into the factors: supervision, physical condition of work, salary benefit, perception of work, personal recognition, and participation in making decision. The results of the correlation calculations revealed the existence of an incidence of workload on job satisfaction in the police service’s members of the UPC in La Maná canton. It was determined through the Spearman's Rho coefficient of 0.989 that there is a strong positive correlation, and the result is corroborated through the calculation by factors of each variable.